Perbedaan Nilai Rerata Vo2 Maks Pada Laki-Laki Antara Pekerja Kantoran Dan Pekerja Yang Terpapar Polusi - Caesar, Aya Fana Oase; , dr. Sri Wahyu Basuki, M.Kes; , dr. Dodik Nursanto (2015)
Background:Regular physical activity has positive effect in people all of their stage of life. Higher activities the higher respiratory rate and air consumption. Resultance of some studies found that air quality that we inhale, affect our health quality. The air quality impact to our lungs and whole cardiorespiratory system. To measure O2 maximum value that conducted to the muscles from lungs we can use VO2 Max test. Objective: This study aim to know the VO2 Max value difference between officer and pollutant exposed worker. Methods:Study design using analytic observational with cross sectional approaches. Each group has 25 samples taken using purposive sampling method. Samples are 20-59 yesrs old men which fulfil the restriction criteria. The difference of the mean value VO2 Max was analyzed using t test of two unpaired groups from SPPS 17.0 for windows. Result: The result shows that there was no significant difference statistically in the mean value VO2 max on men between officer (57,8108 ml/kg weight/min) and pollutant exposed worker (60,2412 ml/kg weight/min). The result of t test two unpaired group has significancy 0,185 (p>0,05). Conclusion: There wqs no significant difference between officer and pollutant exposed worker.